Management of Life-threatening Arterial Cannulation in the Subclavian Artery Using Percutaneous Placement of a Covered Stent - Cinosh Mathew; R. Calton (Research Developments in Medicine and Medical Science Vol. 5, 2023)
Central venous catheterization can lead to the rare but life-threatening complication of inadvertent subclavian artery cannulation. To avoid fatal outcomes, it is crucial to promptly identify and manage this issue using methods such as stent placement, thrombin injection, Angio-Seal, or gel foam embolization. In this case report, we describe a successful percutaneous management of subclavian arterial cannulation by covered stent placement, which was performed without any complications.